Influence of Organizational Culture, Workload and Procedural Justice on Employee Organizational Commitment at Dinas Pendidikan, Pemuda Dan Olahraga Daerah Istimewa Yogyakarta - Muti Mali, Christasula Meysi; Subiyanto, Didik -; SL, M Ahyar (Politeknik Negeri Semarang, 2025)
This research aims to explain the influence of organizational culture, workload, and procedural justice on organizational commitment. This research was conducted on employees of the Yogyakarta Special Region Education, Youth and Sports Department. This research is quantitative research with primary data, taken using a non-probability sampling questionnaire by census of 50 respondents. Data was collected via Google form, then processed using multiple linear regression analysis. The research results show that organizational culture and procedural justice have a significant effect on organizational commitment. Meanwhile, workload has no influence on organizational commitment. It is hoped that the results of this research can be a reference for future researchers who will research at the Yogyakarta Special Region Youth and Sports Education Service.